1970
DOI: 10.1111/j.1476-5381.1970.tb10659.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraventricular 2,4,5‐trihydroxyphenylethylamine (6‐hydroxydopamine) on rat behaviour and brain catecholamine metabolism

Abstract: Summary1. 6-Hydroxydopamine (200 jug injected intraventricularly) caused depletion of noradrenaline from all regions of rat brain within 2 h after injection but depletion of dopamine in the brain was observed only from 2 days after injection. Both catecholamines remained depleted for more than 32 days. 2. Rats treated with intraventricular 6-hydroxydopamine were sedated and lethargic, with reduced spontaneous and exploratory activity, for periods of up to 8 days after injection. Conditioned avoidance respondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…More recently it has been shown that reserpine also decreases the level of p-tyramine in the optic lobe of Octopus (Juorio & Philips, 1975). Administration of 6-hydroxydopamine intravenously to kittens or intraventricularly to mature rats depletes both noradrenaline and dopamine in the brain (Laverty, Sharman & Vogt, 1965;Ungerstedt, 1968;Uretsky & Iversen, 1970;Laverty & Taylor, 1970). …”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been shown that reserpine also decreases the level of p-tyramine in the optic lobe of Octopus (Juorio & Philips, 1975). Administration of 6-hydroxydopamine intravenously to kittens or intraventricularly to mature rats depletes both noradrenaline and dopamine in the brain (Laverty, Sharman & Vogt, 1965;Ungerstedt, 1968;Uretsky & Iversen, 1970;Laverty & Taylor, 1970). …”
Section: Introductionmentioning
confidence: 99%
“…No ptosis was observed and catalepsy was present only in those animals receiving higher doses (25 and 50 ,ug icv). All animals showed a decrease in locomotor activity compared with controls, an observation previously made in the rat by Laverty & Taylor (1970). …”
Section: Effect On the Antinociceptive Activity Of Morphinementioning
confidence: 88%
“…Laverty et al, 1965;Malmfors & Sachs, 1968;Tranzer & Thoenen, 1968) and in the central nervous system (e.g. Uretsky & Iversen, 1969;Laverty & Taylor, 1970). This action is secondary to displacement of endogenous NA and appears to be due to intraaxonal oxidation of 6-OHDA, with consequent production of free radicals and mitochondrial damage (Kostrzewa & Jacobowitz, 1974;Silvka & Cohen, 1985).…”
Section: Discussionmentioning
confidence: 99%